Hematopoiesis in aged female mice devoid of thyroid hormone receptors. Issue 1 (January 2020) - Sánchez, Ángela; Contreras-Jurado, Constanza; Rodríguez, Diego; Regadera, Javier; Alemany, Susana; Aranda, Ana
Abstract : Hypothyroidism is often associated with anemia and immunological disorders. Similar defects are found in patients and in mice with a mutated dominant-negative thyroid hormone receptor α (TRα) and in knockout mice devoid of this receptor, suggesting that this isoform is responsible for the effects of the thyroid hormones in hematopoiesis. However, the hematological phenotype of mice lacking also TRβ has not yet been examined. We show here that TRα1/TRβ -knockout female mice, lacking all known thyroid hormone receptors with capacity to bind thyroid hormones, do not have overt anemia and in contrast with hypothyroid mice do not present reduced Gata 1 or Hif 1 gene expression. Similar to that found in hypothyroidism or TRα deficiency during the juvenile period, the B-cell population is reduced in the spleen and bone marrow of ageing TRα1/TRβ -knockout mice, suggesting that TRβ does not play a major role in B-cell development. However, splenic hypotrophy is more marked in hypothyroid mice than in TRα1/TRβ -knockout mice and the splenic population of T-lymphocytes is not significantly impaired in these mice in contrast with the reduction found in hypothyroidism. Our results show that the overall hematopoietic phenotype of the TRα1/TRβ -knockout mice is milder than that found in the absence of hormone. Although other mechanism/s cannot be ruled out, our results suggest that the unoccupied TRs could have a negative effect on hematopoiesis, likely secondary to repression of hematopoietic gene expression.